Preparation method of high-insulativity ultraviolet curing resin and product thereof
By using high-insulating ultraviolet curing resin in the outer packaging of power battery cells, the problem of insufficient insulation pressure resistance and bonding strength of existing UV glue is solved, and more efficient insulation protection and battery lightweight are achieved, satisfying the satisfaction of The market has strict requirements on power battery packaging.
Patent Information
- Application Number
- CN202411582816.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-01-14
AI Technical Summary
The existing UV glue is insufficient insulating pressure resistance and bonding strength in the outer packaging of power batteries, which cannot meet the increasingly stringent market requirements. The production efficiency of the inkjet process is low and energy consumption is high. The traditional PET blue film packaging process is It is complex and difficult to achieve lightweight and efficient environmental protection of batteries.
Using a high-insulating ultraviolet curing resin, the modified polyester containing hydroxyl groups is prepared by dissolving the reaction of a modified polyester containing hydroxyl groups with a bifunctional isocyanate and a monofunctional hydroxyacrylate, combined with a polymer inhibitor, a catalyst and a dehydrating agent. Polyurethane acrylic resin with low viscosity and good system compatibility is mixed with a photoinitiator and cured by ultraviolet light to form a high insulating protective layer.
It has achieved better insulation voltage resistance and bonding strength on the outer packaging of the power battery cell, meets the requirements of reliability and energy saving and efficiency, improves the safety and reliability of the battery and supports lightweighting of the battery. and the development of efficient and environmental protection.
Abstract
Description
Technical Field
[0001] The invention relates to ultraviolet light-cured polyurethane resin, in particular to a preparation method of high-insulation ultraviolet light-cured resin and a product thereof. Background Art
[0002] UV-curable resins have been widely used in prepolymers of curing systems such as coatings, inks and adhesives. These products can be widely used in printing, chemical, decoration, construction, pharmaceutical, electronic, mechanical and automotive fields. Most UV-curable resin prepolymers contain polyacrylic resins with "C=C" unsaturated double bond structures. These structures containing unsaturated double bonds include vinyl, acryloyl, methacryloyl, etc. According to the different structures, they can be divided into the following types of resins: polyester acrylate resins, polyurethane acrylate resins, epoxy acrylate resins, unsaturated polyester and polyether acrylate resins, etc. Among them, epoxy acrylate resins, polyurethane acrylate resins and polyester acrylate resins are the most widely used.
[0003] Polyurethane acrylate is usually synthesized by a two-step reaction of long-chain diols, polyisocyanates and hydroxy acrylates. Polyisocyanates and long-chain diols have structures with many different characteristics. Using these long-chain diols and polyisocyanates with different structures can obtain products with different structures. Their properties vary greatly, each with its own characteristics and high plasticity. The characteristics of polyurethane acrylate are not distinct, but no matter what the performance requirements are, a relatively suitable resin can be found in the polyurethane system.
[0004] The other two widely used resin prepolymers, epoxy acrylic resin has the advantages of good pigment wettability, good chemical resistance, good weather resistance and low price, but its obvious disadvantage is strong water absorption; polyester acrylic resin has many advantages such as low viscosity, good system compatibility, high substrate adhesion, excellent pigment wettability, low odor, low irritation, better flexibility, etc.
[0005] The new energy vehicle industry has developed rapidly in recent years, and the technologies involved in various related fields are also constantly being upgraded and innovated. On the basis of improving the ultimate performance, attention has been paid to high efficiency, environmental protection, energy conservation and emission reduction. Among them, the packaging and integration of power batteries are crucial links. On the premise of meeting their industrial production, they are required to have high production efficiency, excellent yield, low cost, safety and reliability, and good promotion value of volume utilization. The excellent insulation protection in the outer packaging of power batteries can improve the safety and reliability of the battery, thereby reducing the leakage hazards caused by external erosion. At the same time, it can also improve the volume utilization rate, leaving room for subsequent battery integration upgrades, and help designers achieve the goal of lightweight batteries. The traditional outer packaging protection of battery cells is mainly achieved by wrapping with PET blue film, and the blue film and the aluminum layer of the battery cell are bonded with glue. This method has complex processes, low production efficiency, and high energy consumption. It does not meet the requirements of energy saving, high efficiency and green environmental protection. In addition, it is limited by the performance of glue and the construction process. It is impossible to always ensure the complete fit of the blue film and the aluminum layer of the battery cell, which is easy to cause hollowing and bubbles, and the risk of failure is high, which limits the development of lightweight batteries. Considering the quality reliability and energy-saving and high efficiency of actual terminal applications, the improved packaging protection solution at this stage is the inkjet process. In the inkjet process, UV glue is sprayed to cover the outer layer of the battery cell, and then cured with a UV light source to obtain an insulating protective layer, replacing the PET blue film as the outer protective layer of the battery cell, leaving enough design space for the lightweight development of batteries. According to the inkjet process and performance, the UV glue needs to meet the basic characteristics of reliability requirements such as insulation pressure resistance, boiling resistance, salt spray resistance and bonding strength requirements, while also ensuring that it can be cured quickly.
[0006] However, due to the limitation of the viscosity of UV glue in the existing process, the quality of atomized spray products is unstable, the utilization rate of glue is low, and it is easy to cause waste, and it cannot adapt to the more energy-saving and efficient LED curing process. In addition, due to the limitation of formula performance, the bonding strength and reliability of UV glue are poor, the insulation withstand voltage performance is poor, and the results of aging tests such as boiling water resistance and salt spray resistance are not ideal, which cannot meet the increasingly stringent market requirements. Therefore, on the basis of meeting the reliability performance and bonding strength, how to make UV glue obtain better insulation withstand voltage performance for the outer layer protection of power batteries has become an urgent problem to be solved. Summary of the invention
[0007] In view of the above-mentioned shortcomings, the purpose of the present invention is to provide a method for preparing a high-insulation UV-curable resin and its products, which have better insulation and withstand voltage performance on the basis of meeting reliability performance and bonding strength, so that it can be better used in the insulation protection of the outer packaging of power battery cells.
[0008] The technical solution adopted by the present invention is: a method for preparing a high-insulation ultraviolet curing resin, comprising the following steps:
[0009] Step 1): dissolving a hydroxyl-containing modified polyester;
[0010] Placing the polyester oligomer containing hydroxyl groups that react with isocyanate groups and the first reactive diluent in a container, stirring until the solid is completely dissolved, to obtain a hydroxyl-containing modified polyester; wherein the mass ratio of the polyester oligomer containing hydroxyl groups that react with isocyanate groups to the first reactive diluent is 1:1;
[0011] Step 2): Synthesis of high-insulation UV-curable resin;
[0012] The hydroxyl-containing modified polyester prepared in step 1) is stirred and mixed with the polymerization inhibitor and the catalyst, and the temperature is gradually raised to 50-70°C. When the internal temperature rises to 3-5°C lower than the set temperature, the difunctional isocyanate monomer is gradually added. After the addition is completed, the temperature is raised to 75-85°C and the reaction is carried out for 1-3h. Then, the monofunctional acrylate hydroxyl ester monomer is added, the temperature is raised to 95-105°C, and the reaction is continued for 1-3h. After the reaction is completed, the temperature is lowered to 75-85°C, and a dehydrating agent and a second portion of reactive diluent are added. The synthesized product is a high-insulation UV-curable resin;
[0013] The average molecular weight of the modified polyester containing hydroxyl groups is estimated by the hydroxyl value, and the molar ratio of the modified polyester containing hydroxyl groups to the difunctional isocyanate monomer and the monofunctional acrylate hydroxyl ester monomer is 1 to 1.1:1:1 to 1.1;
[0014] Among them, the inhibitor, catalyst, dehydrating agent and the second active diluent are 2.5-3.5‰, 0.5-1.5‰, 0.5-1.5% and 45-55% of the total mass of the reactants respectively, wherein the total mass of the reactants refers to the total mass of the hydroxyl-containing modified polyester, the difunctional isocyanate monomer and the monofunctional hydroxy acrylate monomer.
[0015] Further, the active diluent is an acrylate monomer, specifically one of benzyl acrylate (BZA), dipropylene glycol diacrylate (DPGDA), tripropylene glycol diacrylate (TPGDA), and acrylic acid morpholine (ACMO);
[0016] The difunctional isocyanate monomer is one of toluene diisocyanate (TDI), hexamethylene diisocyanate (HDI), isophorone diisocyanate (IPDI), diphenylmethane diisocyanate (MDI), and dicyclohexylmethane diisocyanate (HMDI);
[0017] The monofunctional hydroxy acrylate is one or more combinations of hydroxyethyl acrylate (HEA), hydroxyethyl methacrylate (HEMA), hydroxypropyl acrylate (HPA), hydroxypropyl methacrylate (HPMA), and hydroxybutyl acrylate (4-HBA);
[0018] The polymerization inhibitor is one of hydroquinone, p-hydroxyanisole, 2,6-di-tert-butyl-p-cresol, pyrogallol, naphthoquinone and 1,4-benzoquinone;
[0019] The catalyst is dibutyltin dilaurate, one of the polyurethane catalysts;
[0020] The dehydrating agent is a polyurethane dehydrating agent.
[0021] Furthermore, in step 2), the polyester oligomer, the difunctional isocyanate monomer and the monofunctional hydroxy acrylate monomer undergo an addition reaction in the presence of an inhibitor and a catalyst by controlling the feeding order of the polyester oligomer, the difunctional isocyanate monomer and the monofunctional hydroxy acrylate monomer to obtain a polymer in which the isocyanate is connected to the polyester oligomer at one end and the hydroxy acrylate is connected to the other end.
[0022] Furthermore, in step 2), the hydroxy ester of the polyester oligomer is 20-30 mg KOH / g; and the number average molecular weight of the polyester oligomer is 1800-3000 g / mol.
[0023] Further, the method further comprises the following steps:
[0024] 3) preparing high-insulation UV-curable resin curing materials;
[0025] The high-insulation UV-curable resin of step 2) is mixed with an appropriate amount of photoinitiator, stirred evenly, left to stand until bubbles disappear, evenly applied on an aluminum sheet, and irradiated with UV light for 5-10 seconds to obtain a high-insulation UV-curable resin cured material.
[0026] A high-insulation ultraviolet-curable resin prepared by the method for preparing the high-insulation ultraviolet-curable resin.
[0027] The present invention has the following advantages: the polyester-based polyurethane acrylic resin uses polyester oligomers and hydroxy acrylate to end-cap difunctional isocyanate, and the excellent performance provided by the polyester material is retained, so that it has the advantages of good system compatibility, low viscosity, high substrate adhesion, etc. At the same time, the characteristics of the overall polyurethane acrylate material can produce good insulation, making it a UV-curable resin material with a wide range of uses and excellent insulation performance.
[0028] Compared with using epoxy resin as the basic material for insulating properties, epoxy resin has strong water absorption, and the UV-curable material made of it has poor water resistance and high viscosity, which limits its use in the field of power battery ink. The present invention uses a polyester material with low system viscosity and good system compatibility to ensure that the viscosity of the system will not increase while ensuring the insulating properties. Compared with the material made of anhydride grafted polypropylene, although it can still have certain mechanical properties under high temperature conditions, the properties of plastics make it difficult to have use value in the coating and ink industries. Moreover, on the basis of meeting the reliability performance and bonding strength, the present invention has better insulation and withstand voltage performance, so that it has better application in the insulation protection of the outer packaging of power battery cells.
[0029] The present invention will be further described below in conjunction with specific implementation modes. DETAILED DESCRIPTION
[0030] In order to more clearly understand the above-mentioned purpose, features and advantages of the present invention, the present invention is further described below in conjunction with embodiments. It should be noted that the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.
[0031] Example 1
[0032] The preparation method of high-insulation ultraviolet light-curing resin comprises the following steps: adding 600 g of modified polyester with hydroxyl group, 1.95 g of hydroquinone and 0.65 g of dibutyltin dilaurate to an oil bath at a stirring speed of 300-350 rpm, heating the mixture to 55° C., and when the internal temperature reaches about 50° C., dripping 30 g of isophorone diisocyanate into a three-necked flask, heating the mixture to 80° C. and reacting the mixture for 2 h, adding 19.91 g of hydroxy acrylate, heating the mixture to 100° C. and reacting the mixture for 2 h, cooling the mixture to 80° C., adding 6.50 g of a polyurethane dehydrating agent and 324.95 g of a diluent, and discharging the mixture.
[0033] Preparation of high-insulation UV-curable resin curing material: weigh about 10.0g of cooled resin, add 0.4g 819 photoinitiator, mix evenly, wait until the bubbles disappear completely, evenly apply it on the aluminum sheet, and irradiate it under 395nm UV lamp for 5s to make high-insulation UV resin curing material.
[0034] Example 2
[0035] The preparation method of high-insulation ultraviolet light-curing resin comprises the following steps: adding 660 g of modified polyester with hydroxyl group, 2.145 g of p-hydroxyanisole and 0.705 g of dibutyltin dilaurate, heating the oil bath to 70°C at a stirring speed of 300-350 rpm, and when the internal temperature reaches about 65°C, dripping 24.97 g of hexamethylene diisocyanate into a three-necked flask, heating the flask to 80°C and reacting for 2 hours, adding 19.77 g of hydroxy acrylate, heating the flask to 100°C and reacting for 2 hours, cooling the flask to 80°C, adding 7.05 g of a polyurethane dehydrating agent and a diluent, and discharging the flask.
[0036] Preparation of high-insulation UV-curable resin curing material: weigh about 10.0g of cooled resin, add 0.3g of photoinitiator, 0.15g of 184 photoinitiator and 819 photoinitiator respectively, mix well, wait for the bubbles to completely disappear, evenly apply it on the aluminum sheet, and irradiate it under 395nm UV lamp for 5s to make high-insulation UV resin curing material.
[0037] Example 3
[0038] The invention discloses a method for preparing a high-insulation ultraviolet light-curing resin, comprising the steps of: adding 660 g of a modified polyester with a hydroxyl group, 2.16 g of 2,6-di-tert-butyl-p-cresol, and 0.719 g of dibutyltin dilaurate, stirring at a speed of 300-350 rpm, heating an oil bath to 65° C., and when the internal temperature reaches about 60° C., dripping 37.15 g of diphenylmethane diisocyanate into a three-necked flask, heating the flask to 80° C. and reacting for 2 h, adding 21.90 g of hydroxypropyl methacrylate, heating the flask to 100° C. and reacting for 2 h, cooling the flask to 80° C., adding 7.19 g of BF-5 and 359.525 g of tripropylene glycol diacrylate (TPGDA), and discharging the flask.
[0039] Preparation of high-insulation UV-curable resin curing material: weigh about 10.0g of cooled resin, add 0.5g of photoinitiator, 0.25g of 184 photoinitiator and TPO photoinitiator, mix evenly, wait until the bubbles disappear completely, evenly apply it on the aluminum sheet, and irradiate it under 395nm UV lamp for 5s to make high-insulation UV resin curing material.
[0040] The above embodiments were subjected to the following performance tests (see Table 1 for test results), and a comprehensive comparative analysis was performed on the test results.
[0041] Table 1:
[0042] Test items Example 1 Example 2 Example 3 Adhesion Level 0 Level 0 Level 0 hardness 2H H 2H bending pass pass pass Withstand voltage test 10KV 9KV 8.5KV Resistant to boiling pass pass pass
[0043] (1) Adhesion test: The adhesion of the UV-curable resin samples obtained in each embodiment was tested before and after the double 85 aging test according to the method of GB / T 1893.4-2023 (cross-cut adhesion determination method), and the total area of detachment at the edge and intersection of the cutting line was divided into: the cutting edge was completely smooth, and no grid was detached, which was graded as 0; a small amount of paint film detached at the cutting intersection, and the affected cross-cut area was ≤5%, which was graded as 1; the paint film detached at the cutting edge or intersection, and the affected cutting area was greater than 5% and ≤15%, which was graded as 2; the paint film partially or completely detached in large pieces along the cutting edge, and partially or completely detached at different parts of the grid, and the affected cutting area was greater than 15% and ≤35%, which was graded as 3; the paint film detached in large pieces along the cutting edge and partially or completely detached at some grids, and the affected cutting area was greater than 35% and ≤65%, which was graded as 4; any degree of detachment exceeding grade 4 was graded as 5. The results are judged to be qualified when the adhesion is ≥ level 1, thus determining the adhesion of the UV-curable resin double 85 before and after aging. The results are shown in Table 1.
[0044] (2) Hardness test: The UV-curable resin samples obtained in each embodiment are subjected to pencil hardness test with reference to the standard of GB / T6789-2022 before and after the double 85 aging test. The sample is applied to a flat plate with a uniform thickness, then cured and placed in a horizontal position; the pencil is fixed to a mechanical device and pressed down at a 45-degree angle on the coating surface with a load of 750g; the pencil immediately pushes the flat plate after contacting the coating, pushing at least 7mm at a speed of 0.5mm / s-1mm / s; wipe the coating surface and assess the damage (standard: the coating has no scratches of 3mm or more with a hard pencil hardness). The result is judged to be qualified when the hardness is greater than or equal to HB level, thereby determining the adhesion of the UV-curable resin before and after double 85 aging. The results are shown in Table 1.
[0045] (3) Bending test: The UV-curable resin obtained in each example was bent 90° on a 32 mm radius of curvature rod, and the surface state of the adhesive layer was observed. If there were no obvious cracks or damage, it was judged as pass, and if there were cracks or damage, it was judged as NG. The results are shown in Table 1.
[0046] (4) Withstand voltage test: The UV-curable resin obtained in each embodiment was subjected to a double 85 aging test. The samples before and after double 85 aging were tested with a GPT-9803 voltage / insulation resistance tester, DC 4000V 60s, click test, and read the test results. A leakage current of ≤0.1mA was judged as pass, and a leakage current of >0.1mA was judged as NG. The insulation withstand voltage value was read and recorded. The results are shown in Table 1.
[0047] (5) Boiling test: The UV-curable resin samples obtained in each embodiment were placed in boiling water for 72 hours, taken out, wiped dry and placed for 1 hour, and tested for adhesion and withstand voltage. Adhesion ≥ 1 level, withstand voltage test leakage current ≤ 0.1 mA was judged as pass, adhesion < 1 level, withstand voltage test leakage current > 0.1 mA (any of these phenomena) was judged as NG. The results are shown in Table 1.
[0048] It can be seen that the polyester-based polyurethane acrylic resin uses polyester oligomers and hydroxy acrylate to end-cap difunctional isocyanate, and the excellent performance provided by the polyester material will be retained, so that it has the advantages of good system compatibility, low viscosity, and high substrate adhesion. At the same time, the characteristics of the overall polyurethane acrylate material can produce good insulation, making it a UV-curable resin material with a wide range of uses and excellent insulation properties.
[0049] Compared with using epoxy resin as the basic material for insulating properties, epoxy resin has strong water absorption, and the UV-curable material made of it has poor water resistance and high viscosity, which limits its use in the field of power battery ink. The present invention uses a polyester material with low system viscosity and good system compatibility to ensure that the viscosity of the system will not increase while ensuring the insulating properties. Compared with the material made of anhydride grafted polypropylene, although it can still have certain mechanical properties under high temperature conditions, the properties of plastics make it difficult to have use value in the coating and ink industries. Moreover, on the basis of meeting the reliability performance and bonding strength, the present invention has better insulation and withstand voltage performance, so that it has better application in the insulation protection of the outer packaging of power battery cells.
[0050] The present invention is not limited to the above-mentioned embodiments. Other methods for preparing high-insulation UV-curable resins and their products obtained by adopting the same or similar technical features as the above-mentioned embodiments of the present invention are within the protection scope of the present invention.
Claims
1. A method for preparing a high-insulation UV-curable resin, characterized in that: The steps include: Step 1): dissolving a hydroxyl-containing modified polyester; Placing the polyester oligomer containing hydroxyl groups that react with isocyanate groups and the first reactive diluent in a container, stirring until the solid is completely dissolved, to obtain a hydroxyl-containing modified polyester; wherein the mass ratio of the polyester oligomer containing hydroxyl groups that react with isocyanate groups to the first reactive diluent is 1:1; Step 2): Synthesis of high-insulation UV-curable resin; The hydroxyl-containing modified polyester prepared in step 1) is stirred and mixed with the polymerization inhibitor and the catalyst, and the temperature is gradually raised to 50-70°C. When the internal temperature rises to 3-5°C lower than the set temperature, the difunctional isocyanate monomer is gradually added. After the addition is completed, the temperature is raised to 75-85°C and the reaction is carried out for 1-3h. Then, the monofunctional acrylate hydroxyl ester monomer is added, the temperature is raised to 95-105°C, and the reaction is continued for 1-3h. After the reaction is completed, the temperature is lowered to 75-85°C, and a dehydrating agent and a second portion of reactive diluent are added. The synthesized product is a high-insulation UV-curable resin; The average molecular weight of the modified polyester containing hydroxyl groups is estimated by the hydroxyl value, and the molar ratio of the modified polyester containing hydroxyl groups to the difunctional isocyanate monomer and the monofunctional acrylate hydroxyl ester monomer is 1 to 1.1:1:1 to 1.1; Among them, the inhibitor, catalyst, dehydrating agent and the second active diluent are 2.5-3.5‰, 0.5-1.5‰, 0.5-1.5% and 45-55% of the total mass of the reactants respectively, wherein the total mass of the reactants refers to the total mass of the hydroxyl-containing modified polyester, the difunctional isocyanate monomer and the monofunctional hydroxy acrylate monomer.
2. The method for preparing a highly insulating ultraviolet curable resin according to claim 1, characterized in that: The active diluent is an acrylate monomer, specifically one of benzyl acrylate (BZA), dipropylene glycol diacrylate (DPGDA), tripropylene glycol diacrylate (TPGDA), and acrylic acid morpholine (ACMO); The difunctional isocyanate monomer is one of toluene diisocyanate (TDI), hexamethylene diisocyanate (HDI), isophorone diisocyanate (IPDI), diphenylmethane diisocyanate (MDI), and dicyclohexylmethane diisocyanate (HMDI); The monofunctional hydroxy acrylate is one or more combinations of hydroxyethyl acrylate (HEA), hydroxyethyl methacrylate (HEMA), hydroxypropyl acrylate (HPA), hydroxypropyl methacrylate (HPMA), and hydroxybutyl acrylate (4-HBA); The polymerization inhibitor is one of hydroquinone, p-hydroxyanisole, 2,6-di-tert-butyl-p-cresol, pyrogallol, naphthoquinone and 1,4-benzoquinone; The catalyst is dibutyltin dilaurate, one of the polyurethane catalysts; The dehydrating agent is a polyurethane dehydrating agent.
3. The method for preparing a highly insulating ultraviolet curable resin according to claim 1, characterized in that: In step 2), the polyester oligomer, difunctional isocyanate monomer and monofunctional hydroxy acrylate monomer are subjected to addition reaction in the presence of an inhibitor and a catalyst by controlling the feeding order of the polyester oligomer, difunctional isocyanate monomer and monofunctional hydroxy acrylate monomer to obtain a polymer in which one end of the isocyanate is connected to the polyester oligomer and the other end is connected to the hydroxy acrylate.
4. The method for preparing a highly insulating ultraviolet curable resin according to claim 1, characterized in that: In step 2), the hydroxy ester of the polyester oligomer is 20-30 mg KOH / g; and the number average molecular weight of the polyester oligomer is 1800-3000 g / mol.
5. The method for preparing a highly insulating ultraviolet curable resin according to claim 1, characterized in that: The following steps are also included: 3) preparing high-insulation UV-curable resin curing materials; The high-insulation UV-curable resin of step 2) is mixed with an appropriate amount of photoinitiator, stirred evenly, left to stand until bubbles disappear, evenly applied on an aluminum sheet, and irradiated with UV light for 5-10 seconds to obtain a high-insulation UV-curable resin cured material.
6. A highly insulating ultraviolet-curable resin prepared by the method for preparing a highly insulating ultraviolet-curable resin according to any one of claims 1 to 4.
Citation Information
Patent Citations
Ultraviolet cured two-degree-of-functionality polyurethane acrylic ester base coating resin for vacuum coating
CN102604035A
Ultraviolet-curing hyperbranched polyester polyurethane acrylate resin and preparation method thereof
CN107266654A
Ultraviolet light curable high-strength polyurethane acrylate resin and preparation method thereof
CN108383974A